SCHOOL EVALUATION - SOME CURRENT ISSUES - Daniela JEDER (Association of Social and Educational Innovation, 2023)
In the context of the changes registered at the level of education in general and practical pedagogy, in particular, a series of new emphases in school assessment is also registered. Some of the questions that this material tries to answer are: What new elements are registered in the practical space of school evaluation? How do teachers today use formative assessment in the classroom and encourage the use of metacognitive skills that support learning? What is test anxiety and how does formative assessment help reduce it?